Policy Challenges and Implementation Gaps in Arabic Proficiency Testing at Indonesian Islamic State Universities - Raodhatul Jannah; Darmawati Darmawati (Ijaz Arabi Journal of Arabic Learning, 2026)
The implementation of Arabic proficiency testing in Indonesian Islamic State Universities presents several challenges and opportunities for improving students’ language proficiency. This study explores the experiences of students and educators in navigating the Arabic proficiency tests and examines the implications for institutional and pedagogical practices. The study focuses on three major challenges in the implementation of testing policy: (1) inconsistency in testing standards across institutions, (2) misalignment between the test content and the Arabic curriculum, and (3) inadequate institutional support for student test preparation. This study adopts a qualitative case study design of Arabic proficiency testing at the State Islamic Institute of Parepare (IAIN Parepare). Data were collected through policy analysis, test results, and interviews with students from various academic programs.  The findings indicate that students often perceive the test as difficult due to unfamiliar test formats and content that exceeds the curricular scope. Moreover, educators struggle to integrate test-oriented skills into regular instruction due to the lack of clear institutional guidelines. The analysis reveals that, while the tests play a critical role in assessing students’ language skills, these challenges hinder the policy's effectiveness. Despite these challenges, the study offers recommendations for improving the standardization of testing procedures, aligning the curriculum more closely with the tests, and enhancing institutional support to prepare students better. Addressing these issues will help create more equitable and accurate assessments of Arabic proficiency across all institutions.